2006
DOI: 10.3998/ark.5550190.0007.b07
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some new azoles of potential antiviral activity

Abstract: Starting from the pyrazole-4-carboxylic acid hydrazide 3, a variety of new oxadiazoles 7-9, 11, 13, 17, 18, triazoles 20, 22-25, thiadiazole 21 and pyrazole derivatives 26-29 have been synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Traditionally, small molecule compounds are the most commonly used agents during the course of antibacterial therapy [1,2]. Heterocyclic compounds are organic molecules, which include guanidines derived from carbazoles and azoles and have shown good antibacterial effect [3,4]. Metal ions of heterocyclic compounds play a major role in the antibacterial activities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, small molecule compounds are the most commonly used agents during the course of antibacterial therapy [1,2]. Heterocyclic compounds are organic molecules, which include guanidines derived from carbazoles and azoles and have shown good antibacterial effect [3,4]. Metal ions of heterocyclic compounds play a major role in the antibacterial activities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…35 These five-membered heterocyclic rings have also proved to have very effective antiviral activity against a wide range of viruses, making them of great value in the antiviral research. [36][37][38][39][40][41] Tang et al 45 have reported the synthesis of a series of benzothiazole derivatives bearing 1,3,4-thiadiazole moiety. The newly synthesized compounds exhibited good antivirus activity against tobacco mosaic virus, with compound 3 being the most effective.…”
Section: Introductionmentioning
confidence: 99%
“…16 respectively. Among the 1, 3, 4-oxadiazoles, pyrazole containing 2, 5-disubstituted-1, 3, 4-oxadiazoles are found to have considerable interest in medicinal chemistry because of their various biological characterized possessed by these compounds like antimicrobial, 17 antioxidant, 18 DNA photocleavage activity, 19 anticancer, 20 anti-inflammatory 21 and antiviral 22 activities. On the other hand, hydrazones are of considerable interest in synthetic chemistry and are broadly considered for studies as reaction intermediates or reactants since they can readily undergo various ring closure reactions.…”
Section: Introductionmentioning
confidence: 99%